The Effect of Corporate Political Connections on Tax Aggressiveness - Agung Prasetyo Nugroho Wicaksono (Journal of Applied Accounting and Taxation, 2019)
This study examines whether corporate political connections influence tax aggressiveness in state-owned enterprises and private-owned enterprises in Indonesia. The observation period is 2015 to 2017. The population taken is a state-owned enterprise and a non-financial sector private sector business entity with 327 companies with a period of 3 years. Then the determination of the sample using a purposive sampling method used a sample of 148 companies. The results of this study indicate that the existence of political connections in state-owned enterprises and private-owned enterprises has a significant positive effect on tax aggressiveness.